Synthesis of novel lipoic acid derivatives - Juan Pablo González-Gutiérrez; Silvana Moris; Claudio Barrientos (Journal of the Chilean Chemical Society, 2024)
Lipoic acid is a naturally occurring compound involved in biological processes with special reactivity due to its 1,2-dithiolane ring. The novel ALA derivatives were synthesized using the Steglich esterification in mild conditions and then concentrated and neutralized with yields of 45.1 to 81.2%.